Identifying dominant quinones in digested sludge at trace levels using online supercritical fluid extraction–liquid chromatography - Farida Hanum; Mona F. A. Dawood; Yoichi Atsuta; Hiroyuki Daimon (Discover Sustainability)
Abstract Understanding microbial community structure is crucial in environmental research. Consequently, it is essential to develop rapid and efficient methods to analyze microbial community structure in environmental samples containing diverse microorganisms in trace amount. Moreover, some microorganisms are difficult to culture or collect in large quantities. Therefore, this study developed a method focuses on the trace analysis of quinone species in these microorganisms. To address this, we developed an online system that connects supercritical fluid extraction (SFE), known for its highly selective extraction ability using both static and dynamic methods, with liquid chromatography (LC) for quinone separation and determination. A trapping column was installed at the SFE–LC interface. This technique provides highly sensitive determination of quinones because they are analyzed within a closed system, preventing their degradation due to environmental conditions, thus ensuring accurate quantification. The recovery percentage of menaquinone 7 using SFE-LC method was 86.2% of the amount recovered via direct injection without extraction. Furthermore, the method efficiently identified the quinone species in a pure bacterial culture of Moorella sp. Hama 1, which is difficult to culture. A trace-amount sample of 0.005 g, the smallest quantity tested, was successfully profiled; this represents the limit of quantification for quinone profiling using this method. Thus, this method can identify a quinone in a trace sample that is nearly 1/20 the size required by the conventional method (0.1 g). The online SFE–LC technique successfully identified quinone species at trace amounts in three digestive sludge samples at this trace amount (0.005 g). Ubiquinone (UQ)-10, other UQs, menaquinone (MK)-7, MK-8, MK-8(H2), MK-8(H4), MK-9, MK-9(H2), MK-10, MK-10(H2), and MK-10(H4) were the major quinone species identified in the digestates. In the AGREE Analytical Greenness evaluation, the SFE–LC method achieved a high score (0.66), reflecting its efficiency, minimal waste generation, automation, and reduced environmental impact. These results highlight the method’s potential for quinone profiling with simplified device configuration, making it feasible to monitor the microbial composition in trace amounts of biological samples.